Engineering MoS2 Nanosheets Anchored on Metal Organic Frameworks Derived Carbon Polyhedra for Superior Lithium and Potassium Storage - Rui, Binglong; Li, Jiahui; Chang, Limin; Wang, Hairui; Lin, Li; Guo, Yu; Nie, Ping (Frontiers in Energy Research, 2019)
Metal organic frameworks (MOFs) have exhibited promising potential as a new platform for the preparation of porous functional materials for energy storage application. Herein, we report an approach to synthesize ultrathin MoS2 nanosheets decorated cobalt nanoparticles-containing porous carbon polyhedral with dense nitrogen doped carbon nanotubes (CNTs) backbone, where the ZIF-67 is used as the carbon and nitrogen sources for the growth of CNTs and the self-template for the carbon polyhedron. The composite shows a unique structure in which ultrathin MoS2 nanosheets are uniformly coated on the ZIF-67 derived carbon polyhedron. Owing to the synergistic effect from composition, morphology, and robust hollow structure composed of interconnected nitrogen doped CNTs networks and cobalt particles, the resulting ZIF-67-C@MoS2 nanocomposites display high specific capacity of 568.5 mAh g−1 at a current density of 0.2 A g−1, superior rate capability (291.9 mAh g−1 at 5 A g−1), and excellent cycling stability for over 500 cycles as lithium ion batteries anodes. The material also exhibits superior performance as new anodes for potassium ion batteries. The results provide a facile strategy for large-scale synthesis of high performance anode materials through low cost perspective and new insights for designing MOF-derived functional materials with unique structures for energy storage.